Curriculum for the Imaging of Retroperitoneal Masses and Disease Spread With Anatomic Correlation - Saeed Elojeimy; Mariam Moshiri; Puneet Bhargava; Sherif Osman; Charles Rohrmann (MedEdPORTAL, 2013)
Abstract Introduction Retroperitoneal anatomy is very complex. We wanted to create a presentation that would simplify this subject and show examples of illustrations highlighting the multiple retroperitoneal fasciae and planes, as well as their corresponding appearance on cross-sectional CT imaging. Methods This PowerPoint presentation was designed primarily for radiology residents and faculty but can be used by anyone in the medical field who is interested in radiologic imaging and retroperitoneal anatomy. The presentation provides an overview of the complex retroperitoneal anatomy, with multiple illustrations of the retroperitoneal fasciae, spaces, and interfascial planes. It also discusses the pattern of disease spread in the retroperitoneum, provides a broad overview of the different types of retroperitoneal masses, and proposes an algorithmic approach for diagnosis of retroperitoneal masses based on imaging findings. A number of slides are dedicated to illustrating the role of imaging-guided procedures (mainly biopsies) utilized in the diagnosis and treatment of retroperitoneal masses. Finally, the multisystemic syndromes that involve the retroperitoneum are reviewed in a quiz format. The presentation takes from 30 to 60 minutes depending on the user's prior knowledge of retroperitoneal disease. Results This presentation was presented as an educational exhibit at the Radiologic Society of North America meeting in Chicago, Illinois, and as an exhibit at the imaging symposium at the University of Washington and received positive feedback. Many residents recommended that it would be very helpful for the presentation to be accessible online as a general reference and quick refresher for an overview of retroperitoneal disease. Discussion This presentation requires that the user have some basic understanding of radiology and imaging. The retroperitoneal pathology is very wide; in this presentation, we focus mainly on the pathology with interesting radiologic findings.